ChemInform Abstract: Pd‐Catalyzed Oxidative Annulation of Hydrazides with Isocyanides: Synthesis of 2‐Amino‐1, 3, 4‐oxadiazoles. Issue 45 (23rd October 2014) - Fang, Tao; Tan, Qitao; Ding, Zhengwei; Liu, Bingxin; Xu, Bin
Abstract The Pd‐catalyzed oxidative annulation of acetyl substituted hydrazides (I) through sequential isocyanide insertions into N‐H and O‐H bonds to afford 1, 3, 4‐oxadiazoles (III) in good yields is developed.